Pengaruh Foreign Direct Investment, Inflasi, dan Pengangguran terhadap Ketimpangan Pendapatan dengan Corruption Perception Index sebagai Variabel Moderasi - Wairooy, Fatimah Azzahra; Slamet Haryono, (Jurnal Magister Ekonomi Syariah, 2023)
ABSTRACT This study aims to analyze the effect of Foreign Direct Investment (FDI), inflation, and unemployment on income inequality with the Corruption Perception Index (CPI) as a moderating variable for the 2012-2021 period in eight developed countries. Hypothesis testing using MRA regression. This study took secondary data from The World Bank and Transparency International (TI), in this study using 80 samples obtained from 8 countries consisting of Bangladesh, Egypt, Indonesia, Iran, Malaysia, Nigeria, Pakistan, and Turkey. The results of the study show that Foreign Direct Investment (FDI) has a significant negative effect on income inequality and unemployment has a significant positive effect on income inequality while inflation has no effect on income inequality. In addition, the moderating variable used, namely the Corruption Perception Index (CPI), proved unable to moderate the three independent variables used in this study. The main contribution of this research is that it can provide good indicators for decision-makers in developing countries in terms of increasing FDI, increasing employment, overcoming inflation, and reducing the level of corruption so that later it can help prevent income inequality in developing countries.